Revising Protein Corona Characterization and Combining ITC and Nano-DSC to Understand the Interaction of Proteins With Porous Nanoparticles - Balmori, Alba; Sandu, Romica; Gheorghe, Daniela; Botea-Petcu, Alina; Precupas, Aurica; Tanasescu, Speranta; Sánchez-García, David; Borrós, Salvador (Frontiers in Bioengineering and Biotechnology, 2021)
The exposure of nanoparticles (NP) to biological fluids leads to the formation of a protein coating that is known as protein corona (PC). Since PC formation is influenced by the physicochemical properties of the nanoparticles, the understanding of the interplay of the factors that participate in this process is crucial for the development of nanomaterials as cell targeted delivery vehicles. In general, it is accepted that PC formation is a complex and dynamic process, which depends on the composition of the medium and the properties of the NP mainly size, shape and superficial charge. Interestingly, although the interaction between the protein and the NP is essentially a superficial phenomenon, the influence of the roughness of the nanoparticle surface has only scarcely studied. In this work, the influence of superficial roughness and porosity has been studied with the aid of Nano Differential Scanning Calorimetry (Nano DSC) and Isothermal Titration Calorimetry (ITC) using mesoporous silica nanoparticles (MSNs) as NP model. The interaction process of the proteins with NP surface was analyzed by ITC measurements, while the stability and denaturation of the proteins was monitored with Nano DSC. Thanks to the complementarity of these two techniques, a more complete insight of the PC formation onto the pores has been accomplished.